PROSPECTS FOR DEVELOPMENT AND IMPROVEMENT OF THE MECHANISM OF FUNCTIONING OF THE STOCK MARKET - KADIROVA, KHADICHA (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article analyzes modern trends in the development of the stock market of the Republic of Uzbekistan. The main problems hindering its development are considered. Solutions to some of the existing problems are presented, and priority areas for further development and improvement of the mechanism of functioning of the stock market are determined.